2004
DOI: 10.1021/jp049618b
|View full text |Cite
|
Sign up to set email alerts
|

What Can Really Be Learned from Dielectric Spectroscopy of Protein Solutions? A Case Study of Ribonuclease A

Abstract: We report on a dielectric relaxation study of aqueous solutions of ribonuclease A at 298.15 K as a function of protein concentration between 0.5 and 6 wt % in the MHz/GHz frequency range. The spectra can be decomposed into five modes of Debye type diffusive behavior. In agreement with the standard interpretation, we assign the two dominant modes at low and high frequency (β-relaxation and γ-relaxation, respectively) to protein tumbling and bulk water relaxation. We observe three further modes (δ1−δ3) between β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
254
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(278 citation statements)
references
References 57 publications
20
254
2
2
Order By: Relevance
“…We find that the high-concentration data is consistent with peptide-driven motions of the first hydration layer, while the low-concentration data introduces a new reorientational motion that is solely due to hydration water dynamics, involving dynamic coupling between inner and outer hydration layers and consistent with the shorter time scale δ-dispersion. [42][43][44][45]47 Together, these results suggest that the faster component of the δ-relaxation could be made to disappear for proteins under severe hydration conditions. 47 Our QENS measurements and interpretation may also be consistent with those observed in the TDFSS profile (if relaxation due to the protein environment can be unambiguously removed).…”
Section: Elastic Incoherent Structure Factormentioning
confidence: 91%
See 2 more Smart Citations
“…We find that the high-concentration data is consistent with peptide-driven motions of the first hydration layer, while the low-concentration data introduces a new reorientational motion that is solely due to hydration water dynamics, involving dynamic coupling between inner and outer hydration layers and consistent with the shorter time scale δ-dispersion. [42][43][44][45]47 Together, these results suggest that the faster component of the δ-relaxation could be made to disappear for proteins under severe hydration conditions. 47 Our QENS measurements and interpretation may also be consistent with those observed in the TDFSS profile (if relaxation due to the protein environment can be unambiguously removed).…”
Section: Elastic Incoherent Structure Factormentioning
confidence: 91%
“…[58][59][60][61][62][63][64][65] There is some disagreement as to whether the large range of time scales measured by these techniques, from tens of picoseconds to hundreds of nanoseconds, is actually directly attributable to the hydration layer nearest the protein or peptide surface or to outer hydration layers or even coupling of the hydration dynamics to different components of the solute motion. 18,47,66,67 Although there is agreement that the protein surface hydration layer dynamics are very heterogeneous, there is little information as to which components of the protein surface chemistry contribute to this heterogeneity. At present, a molecular interpretation is needed that would specify the chemical features of the protein surface, the distinct hydration layers ranging from protein surface waters to outer hydration layers to bulk liquid as well as the dynamics of the biological solute, to explain the large dynamic time scale range that is observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frood and Gallagher discovered that the experimental results of the frequency response of liquid are in agreement with Coelho's theory only when an additional contribution to the permittivity arising from DC conductivity has been taken into account [37]. It has been reported that if the polarization induced from DC conductivity is added to the total polarization, a better fit to the experimental results can be achieved [37][38][39][40][41]. In our previous work, a model has been proposed for oil dielectric response in frequency response with two types of charge carriers being involved [42][43][44].…”
Section: Introductionmentioning
confidence: 81%
“…Introduction). Traditional dielectric spectroscopy of protein solutions 56,57 shows that protein/water interfaces have unique dielectric behaviors, different from that of bulk water. Simulations have also shown that the average dielectric permittivity of interfaces tends to be lower than that of the bulk solution.…”
Section: Discussionmentioning
confidence: 99%